Analisis Ekonomi Pemeliharaan Broiler dengan Pemberian Tepung Daun Mengkudu (Morinda citrifolia L.) - D M Ningsih; A Sofiana; N Irwani (Politeknik Negeri Lampung, 2022)
Alternative feed ingredients that can replace commercial feed ingredients such as corn namely noni (Morinda citrifolia L.) leaf which has a high enough metabolic energy content. This study aims to analyze the economics of the application Morinda citrifolia L. in broiler feed. This research was conducted in the broiler cage at Lampung State Polytechnic. In this study, there were four treatments that are T1 application Noni (Morinda citrifolia L.) leaf 0%, T2 application Noni (Morinda citrifolia L.) leaf 2%, T3 application Noni (Morinda citrifolia L.) leaf 4% and.T4 application Noni (Morinda citrifolia L.) leaf 6%. The results of the research on the application Noni (Morinda citrifolia L.) as much 2% in broiler feed is able to reduce production costs. Analyze of Break Even Point (BEP) product 15,16 kg, Break Even Point (BEP) price Rp 21.265,39, Income Over Feed Cost (IOFC) Rp 676.226,00, Revenue Cost Ratio (R/C) 1,74 and Benefit Cost Ratio (B/C) 0,74.